Ecocriticism in Doraemon: Nobita's Earth Symphony - Astuti, Septia Budi; Hastuti, Nur (Proceedings International Conference of Culture and Sustainable Development; Vol 3 (2025): PROCEEDINGS ICOCAS, 2025)
This study analyzes Doraemon: Nobita's Earth Symphony (2024) through Greg Garrard's ecocritical lens, analyzing how the film represents environmental issues using the metaphor of black noise symbolizing ecological degradation. Using qualitative descriptive analysis, the research explores four ecocritical concepts: pollution, apocalypse, dwelling, and earth. Pollution is depicted as black noise disrupting natural harmony. Apocalypse is shown through environmental crisis narratives. Dwelling is portrayed through contrasts between destructive versus harmonious ways of living with nature. In terms of earth is presented as a grand orchestra producing a "symphony of life". A thorough assessment of conversations, visual imagery, and narrative aspects, the research demonstrates how this animated film effectively communicates complex ecological messages through music and visual storytelling. The findings suggest thatÂ  Doraemon: Nobita's Earth Symphony not only presents environmental criticism but also offers an optimistic solution by promoting harmony among living beings to restore ecosystem balance. This research contributes to understanding how popular animated media can enhance ecological awareness among viewers while also serving as an accessible and engaging platform for environmental advocacy that reaches diverse segments of society, particularly children who represent the future stewards of our planet.
Keywords: Ecocritism, Film Animation, Doraemon: Nobitaâ€™s Earth Symphony, Greg Garrad.